Interferon‐γ/CCR5 expression in invariant natural killer T cells and CCL5 expression in capillary veins of dermal papillae correlate with development of psoriasis vulgaris. (1st May 2014) - Kono, F.; Honda, T.; Aini, W.; Manabe, T.; Haga, H.; Tsuruyama, T.
Summary: Background: There have been extensive studies regarding which types of T lymphocytes are involved in psoriasis vulgaris (PV). However, it has remained unclear which types of T lymphocytes might directly contribute to psoriasiform epidermal and vascular hyperplasia. Objectives: To understand the role of T‐cell receptor (TCR)Vα24+ invariant natural killer (iNK)T cells in the development of PV. Methods: Seventeen patients were enrolled in this study. Using biopsy samples of PV plaques, TCRVα24 + iNKT cells were investigated regarding their cytokine production to understand their roles in development of disease. Results: The number of interferon (IFN)‐γ+ iNKT cells correlated with the length of the psoriasiform hyperplasia rete ridge and the Psoriasis Area and Severity Index. IFN‐γ+ iNKT cells in psoriatic skin exhibited higher C‐C chemokine receptor (CCR)5 expression, and the amount of C‐C chemokine ligand (CCL)5, a ligand for CCR5, was increased in capillary veins of psoriasis plaques. CCR5+ iNKT‐cell numbers significantly correlated with the number of capillary vein endothelial cells expressing CCL5 in PV. Furthermore, the number of CCL5+ capillary veins correlated with the maximum rete ridge length. Conclusions: IFN‐γ/CCR5 expression in iNKT cells and CCL5 expression in vessels of dermal papillae correlate with the development of psoriasiform hyperplasia and microabscess. We propose that these iNKT cells may become useful targets for development of novel therapeutic approaches to PV.